Developing an employee engagement strategy for Sparta Foods (Pty) Ltd - Botes, Christine M. (University of the Free State, 2018)
The main objective of this study was to develop an employee engagement strategy for Sparta Foods (Pty) Ltd. To achieve this objective, the researcher firstly conceptualised the construct of employee engagement to gain a better understanding of the different approaches and definitions relating to this concept. The dimensions of engagement were researched and the different models of engagement studied. It was established that four levels of engagement can be distinguished. In order to determine the current levels of engagement within the organisation, the researcher studied the models of measurement of engagement. Employee engagement is closely linked to organisational performance outcomes. If an organisation can improve its levels of engagement, it can lead to higher productivity, profitability, and employee retention. If employees are not engaged, and the organisation does not address this, it could not only cost the organisation in monetary value, but also contribute to lost managerial hours spent on improving the levels of employee performance. Low levels of employee engagement could have a significant impact on the employee turnover of an organisation, morale in the office, quality of products, and word-of-of-mouth promotion. For this quantitative research study, a positivist epistemological approach was followed. Stratified random sampling was used to sample the total population, which consisted of 792 employees. A random sample size of 400 was selected. The Utrecht Work Engagement Scale (UWES) questionnaire was used for the collection of the primary data. Some of the questionnaires were web-based and the remainder of the questionnaires were hard copies that were distributed by each head of department (HOD) in the organisation. The overall results of the study indicated that the majority of the respondents were engaged. This means that the majority of the workforce has a positive attitude, but they are not entirely action orientated. The dimensions that scored high negative scores were vigour and absorption. The high negative scores for vigour indicated that some of the employees did not have a positive feeling of physical strength, emotional energy, and cognitive liveliness that arise in response to their evaluation of the work they do. They also do not feel personally fulfilled by the work that they do and it does not excite or invigorate them. Employees are thus unwilling to go the extra mile for the organisation and get tired easily when doing their jobs. The respondents did not feel like going to work in the morning and did not have high levels of energy and mental resilience. The high negative scores for absorption, on the other hand, indicate noncommitment and a lack of involvement by employees in their jobs. The employees are not immersed in their jobs and for a large percentage, their job is only a means to an end. These employees are not committed, are not inclined to put much effort into their work, and have no interest in the organisation or a desire to stay there. To increase the level of engagement to actively engaged, the researcher proposed an input strategy of performance appraisals, training, and communication, which would deliver an output of job satisfaction, career progression, and innovation for employees, and employee retention, customer satisfaction, and growth and profitability for the organisation.
Dissertation (MBA (Business Administration))--University of the Free State, 2018